PENGARUH MODEL PEMBELAJARAN MAKE A MATCH TERHADAP MOTIVASI BELAJAR PEMBELAJARAN TEMATIK-INTEGRATIF KELAS IV SD NEGERI DONOROJO 2 DEMAK - Fajar Cahyadi; Putri Ambarwati (Malih Peddas (Majalah Ilmiah Pendidikan Dasar), 2015)
Problems studied in this research is whether there is influence learning model to Make a Match motivation and learning thematic integrative Elementary School fourth grade SD N Donorojo 2 Demak school year 2013/2014? Goals to be achieved in this study was to investigate the influence of the learning model to Make a Match integrative motivation to learn thematic Elementary School fourth grade SD N Donorojo 2 Demak academic year 2013/2014 views of learners' learning motivation after the treatment.This research is quantitative. The population in this study is the fourth grade students of SD Negeri Donorojo 2 Demak . Samples taken that whole fourth grade students totaling 24 learners using the technique of saturated samples. The design of this study used a pre-experimental design (nondesign) in the form of a one- group pretest-posttest design. The data in this study were obtained through questionnaires, documentation and observation sheet. Data analysis technique used is using t-test and a test to determine the normalized gain increased motivation of learners.The data has been collected and analyzed using t-test and test normalized gain. In the t-test obtained t of 6.375 ?óÔÇ??Ñ 2.069 ttable with siginfikasi 5% level. So H0 is rejected and Ha is accepted or it can be said that this study shows the difference between the initial conditions and the improvement of the condition of significant end. So in this study it can be concluded that no effect of the use of learning models to Make a Match motivation and learning thematic integrative Elementary School fourth grade SD N Donorojo 2 Demak school year 2013/2014. Normalized gain calculations indicate the magnitude of the increase in motivation of learners prior to the treatment of learning models Make a Match and after treatment learning model to Make a Match. Pretest and posttest results obtained with a gain of 0,75 higher category.Thus the suggestion that teachers should convey the researcher can use the Make a Match model of learning in the learning activities specially integrated thematic learning to make learning atmosphere becomes more active, innovative, creative, effective and fun.